AN ANALYSIS OF STUDENTS’ ABILITY IN CONSTRUCTING INFORMATION QUESTION - Adila Destrianti; Adnan Aryuliva; Fitrawati - (Universitas Bengkulu, 2016)
Constructing information question with correct grammar is an ability that should be owned by the students. The aim of this research is to find out the research question about how the students’ ability in constructing information question is. This is a descriptive research. The data were collected from twenty-eight students of eighth grade of SMP 30 Padang that were chosen randomly. This research used test as the instrument that consist of twelve question tests that represent question word what, where, who, why, when, and how. Analysis data based on indicators of information question; question word, auxiliary verb, subject, main verb, and sentence complement. From the result of this study, it was gained that students’ abilities were very good in determining question word, not very good in determining auxiliary verb, good in determining subject, not good in determining verb, and average in determining complement. It can be concluded that students have good ability in determining question word, subject, and complement in constructing information question, while students still have low ability in determining auxiliary verb and verb in constructing information question.